Consumer Perception Analysis On The Brand Equity Of Shampoo Sunsilk And Pantene In The City Of Medan - Muhammad Zuardi (Proceeding International Seminar of Islamic Studies, 2019)
Brands with strong brand equity can maintain market share, attract investors and fend off the arrival of new competitors. Brand equity consists of elements of brand awareness, brand associations, perceived brand quality and brand loyalty. Sunsilk and Pantene are shampoo brands that have been trusted by most Indonesian people. Both of these shampoos are also in demand and have a strong place in the minds of consumers, especially in the city of Medan. This study aims to determine whether there are differences in brand equity of Sunsilk and Pantene brand shampoo products to consumers in the city of Medan. The results showed there were differences in brand equity of Sunsilk brand shampoo products with Pantene brand shampoo products, where the value of brand equity in Sunsilk brand shampoo was lower compared to Pantene brand shampoo. However, this difference did not occur insignificantly.